Atypical pleomorphic adenoma with chronic sialoadenitis of the submandibular gland: a case report in a child - Andrea Satta; Filippo Carta; Carlo Ripoli; Anna Maria Nurchi; Roberto Puxeddu; Gavino Faa; Clara Gerosa (Hygeia Press di Corridori Marinella, 2017)
A 12-year-old girl presented with an oval swelling in the left submandibular region. The tumor had gradually increased in size, during the last 9 months. Preoperative ultrasonography evidenced an hypoechoic oval mass, 14 x 12 mm in size. Submandibulectomy was performed. At macroscopy, the tumor was surrounded by a fibrous capsule, and appeared tan-white in color. At histology, an admixture of epithelial and mesenchymal cell components characterized the tumor. Epithelial cells showed large polymorphous atypical nuclei, with irregular nuclear membranes. The mesenchymal cells were embedded in a myxoid matrix, with focal areas of chondroid differentiation. The tumor showed pushing margins, focally extending into the fibrous capsule. Occasionally, some scattered foci of capsular pseudo-infiltration were detected. The proliferative index of tumor cells, detected by Ki67 immunostaining, reached levels around 10% in some tumor areas characterized by the highest frequency of atypical tumor cells. On these bases, a diagnosis of atypical pleomorphic adenoma was performed. A lymphocytic infiltrate, sometimes organized in lymphoid nodules, was observed in the surrounding submandibular gland. After 1 year of follow-up, the patient is in good health, in the absence of any recurrence. The case here reported confirms that tumors of the salivary gland occurring in children are characterized by a higher aggressive potential, here represented by the atypical tumor cells associated with the high proliferative index and with the pressure on the tumor capsule, and deserve the complete resection of the affected salivary gland, in order to prevent their potential malignant transformation. The association of the salivary gland tumor presenting in our patient with lymphocytic nodular sialoadenitis confirms previous reports of this peculiar association, and reinforces the hypothesis that the two conditions might share a common etiology.